Media Kriya Bahasa: Integrasi Seni dan Literasi Multimodal dalam Pembelajaran Bahasa Indonesia - Tahmida, Nova Shufia (Paedagogie, 2025)
This study aims to describe the implementation of language craft media as a form of art integration and multimodal literacy in Indonesian language learning. The research subjects were student teachers who designed and developed craft-based learning media, namely word collages, creative text cards, and narrative visual works. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of language craft media products. The results showed that word collages enriched vocabulary and reading skills, creative text cards encouraged the ability to write simple sentences with visual support, while narrative visual works integrated writing and speaking skills multimodally. These findings indicate that language craft media can expand the learning experience of student teachers in designing Indonesian language learning that is creative, contextual, and in accordance with the demands of multimodal literacy. This study provides implications that the integration of art and language needs to be developed as an alternative learning media that is relevant in the contemporary education era.